Struggles of village-owned enterprise to improve performance: A case in Kupang Regency, Indonesia - Petrus Kase; Yaherlof Foeh; Adriana Rodina Fallo; Melania Tawa; Juwita S. Kariam (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This research assessed the struggles of the village-owned enterprise of Raknamo Village in Kupang Regency, East Nusa Tenggara Province, to enhance performance.Design/Methodology/Approach: This research used a qualitative approach consisting of stages, such as data collection, data reduction, data display, and conclusion drawing. It collected data through in-depth interviews, non-participant observation, and document review. It analyzed data on performance indicators: resource provision, task implementation, outputs, and goal attainment that the village-owned enterprise struggles to accomplish.Research findings: This research uncovered that the village-owned enterprise of Raknamo Village faces difficulties even now, thus generally performing low in its efforts to provide resources needed, such as personnel, finances, and facilities, implement tasks, produce outputs/products, and attain goals. Specifically, it performed relatively well in renting tents and chairs, increasing little profit; however, it performed poorly in the savings and loan business and traditional weaving home industry, thus experiencing financial loss. The primary factors affecting such performance were the core managers' low managerial and entrepreneurial skills, financial inability and low cooperative attitude of the village society to repay loans, inability of village society to do profitable business, and low income.Theoretical contribution/Originality: This research evaluated the struggles of the village-owned enterprise of Raknamo Village in Kupang Regency to boost performance, which prior studies have not widely investigated. Theoretically, this research is expected to add specified academic or analytical insight into the village-owned enterprises struggling as small business organizations to improve performance.Practitioner implication: The finding has profound implications that eliminating difficulties that hinder the village-owned enterprise’s performance and building its ability to perform better hereafter are both necessary. To reach this expectation, the government should create a capacity-building program for the village-owned enterprise.